Introducing Entrepreneurship in Engineering Education - Burade, K. D. (Journal of Engineering Education Transformations, 1995)
Entrepreneurship can be described as a creative and innovative response to the environment. Today's economy is demanding more entrepreneurs and in the present situation to emerge as successful entrepreneur is a challenge, which needs careful development of the personality. Engineering students are having required knowledge and they can be developed and moulded to become an entrepreneur through implementation of systematically planned EDP in engineering colleges. This paper discusses the objectives and goals . of introducing entrepreneurship in the engineering institutions. It also presents' the strategies of implementation of EDP in engineering colleges.